THEORETICAL RESEARCH OF THE EXTERNAL TEMPERATURE INFLUENCE ON THE TRACTION AND SPEED PROPERTIES AND THE FUEL ECONOMY OF CARGO-CARRYING VEHICLES - Kulmukhamedov, Zhasur; Khikmatov, Ravshan; Saidumarov, Alisher; Kulmukhamedova, Yulduz (Journal of Applied Engineering Science, 2020)
The manuscript proposes analytical methods for calculating fuel economy and traction-speed properties when modeling the movement of cargo-carrying vehicles on real routes, based on theoretical and experimental studies in a hot and dry climate, which allows for determining the efficiency of cargo-carrying vehicles objectively in terms of traction and speed, fuel and economic indicators. Using the statistical processing of experimental, theoretical research data, the authors calculate the coefficient X2, which allows for evaluating the adequacy of the mathematical model and experimental data. As an example, the manuscript provides for an assessment of fuel economy and traction and speed properties. The authors presented the results in graphs for the ease of evaluating the effect of external temperature on fuel consumption and the average speed of a road train. The authors’ methodology allows for determining the efficiency of cargo-carrying vehicles in a hot and dry climate.